Antioxidant and Protease Activities of Seven Native Plant Sources - Rao, Y. Vasudeva; Raju, Merrine (International Journal of Bio-resource and Stress Management, 2016)
The in-vitro antioxidant activity and protease activity of the latex of different plant sources, namely Tabernaemontana divericata, Croton bonplandianum, Plumeria rubra, Nerium oleander, Cascabela thevetia, Alstonia scholaris, Allamanda cathartica were analysed. The antioxidant activity was analyzed using DPPH (1-1, dipenyl-2-picrylhydrazyl) reduction assay and protease activity was analyzed by the cleavage of milk protein, casein. From the results, it was observed that Croton bonplandianum latex has exhibited very strong and highest antioxidant activity (76±5.4%) followed by Allamanda cathartica (71±3.8%). Nerium oleander (62±4.2%) and Plumeria rubra latexes (58±2.9%) have showed good antioxidant activity. Cascabela thevetia (35±4.4%) and Tabernaemontana divericata latexes (28±3.0%) have showed moderate antioxidant activity. However, Alstonia scholaris latex has showed the least and negligible antioxidant activity (0.19±0.05%). The protease activity was found to be significantly highest in the Tabernaemontana divericata latex (4461.55±230 µg ml-1) followed by Cascabela thevetia (3307.7±284 µg ml-1). Good amount of the protease activity was found in Allamanda cathartica latex (1205.15±155 µg ml-1) followed by Croton bonplandianum (923.1±213 µg ml-1). Moderate amount of the protease activity was found in Nerium oleander (333.35±84 µg ml-1) and Plumeria rubra latexes (179.5±38 µg ml-1). However, least protease activity was observed in Alstonia scholaris latex (51.3±14 µg ml-1). The results revealed that almost all plant latex samples except A. scholaris have showed from moderate to strong antioxidant and protease activities. C. bonplandianum latex has exhibited significantly highest antioxidant activity and T. divericata latex has exhibited significantly highest protease activity.